2022
DOI: 10.30813/bmj.v18i2.3286
|View full text |Cite
|
Sign up to set email alerts
|

Persepsi Kemudahan dan Kebermanfaatan dalam Penggunaan Aplikasi Simpan Pinjam Online di Koperasi Karunika: Studi Pendahuluan

Abstract: <p>Karunika is a cooperative at Universitas Terbuka (UT) which members consists of employees of UT. In February 2021, Karunika launched an online savings and loan application (aplikasi simpan pinjam online) to make it easier for members to make savings and loans. This preliminary study aims at collecting information about perceived ease of use and perceived usefulness in affecting attitudes and interest in using “simpan pinjam online” application at the Karunika Cooperative. This study is qualitative res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 6 publications
2
2
0
Order By: Relevance
“…In other words, even while employees find this application to be simple and helpful, their attitude about using it is unaffected because there may lack of beliefs among the members of Karunika in the successfulness of utilizing the application. This is in accordance with [43] study which interviews members of Karunika and found that almost all of senior members feel that they did not have a positive attitude toward the use of application, although they know that the use of the application is easy. Therefore, the fifth hypothesis is not supported.…”
Section: Results and Analysissupporting
confidence: 89%
See 3 more Smart Citations
“…In other words, even while employees find this application to be simple and helpful, their attitude about using it is unaffected because there may lack of beliefs among the members of Karunika in the successfulness of utilizing the application. This is in accordance with [43] study which interviews members of Karunika and found that almost all of senior members feel that they did not have a positive attitude toward the use of application, although they know that the use of the application is easy. Therefore, the fifth hypothesis is not supported.…”
Section: Results and Analysissupporting
confidence: 89%
“…There are many factors that can impact the attitude, makes the PEOU less important to form the positive attitude toward the application. Moreover, the older members of Karunika stated that they have a hesitation of whether they can be succeed in utilizing such application [43] In addition, the overall results of this study confirm TAM model proposed by [32]. However, this study has some limitations.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations